2011
DOI: 10.1007/s00213-011-2459-1
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus accumbens and delay discounting in rats: evidence from a new quantitative protocol for analysing inter-temporal choice

Abstract: Destruction of the AcbC increased the rate of delay discounting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…This suggests that the lesion did not alter the incentive value of the food reinforcer, a conclusion that is in accord with recent interpretations of the effect of AcbC lesions on inter-temporal choice behaviour (Bezzina et al 2007;Valencia-Torres et al 2012). However, visual inspection of the parameter values shown in Fig.…”
Section: Effects Of Antipsychotic Drugs (Olarte Sánchez Et Al 2012a)supporting
confidence: 86%
“…This suggests that the lesion did not alter the incentive value of the food reinforcer, a conclusion that is in accord with recent interpretations of the effect of AcbC lesions on inter-temporal choice behaviour (Bezzina et al 2007;Valencia-Torres et al 2012). However, visual inspection of the parameter values shown in Fig.…”
Section: Effects Of Antipsychotic Drugs (Olarte Sánchez Et Al 2012a)supporting
confidence: 86%
“…The results provide some direct evidence indicating that changes in reward magnitude and delay can impact the observed effect of NAc lesions and concurs with the present findings in the NAc lesion group. In contrast, previous research using adjusting delay schedules has suggested that NAc lesions do not disrupt sensitivity to short-term changes in delay [24, 26]. Due to the inherent oscillations in choice parameters in adjusting delay schedules, these latter studies employed Fourier transform analyses to show that the periodicity of these oscillations was not affected by NAc lesions, thus concluding that NAc lesions did not impair rats’ ability to detect local changes in reward delay.…”
Section: Discussionmentioning
confidence: 84%
“…Both permanent and reversible NAc lesions increase impulsive choice in rats [2326]. NAc lesions have been suggested to diminish rats’ sensitivity to changes in the delay to reward [27], such that the NAc may be critical for the discounting of reward value due to overestimation of reward delays [3, 2832].…”
mentioning
confidence: 99%
See 2 more Smart Citations